ANALISIS PERANAN INDUSTRI PUPUK DALAM MEMPENGARHI SEKTORSEKTOR EKONOMI - Zulkifli (SEKOLAH PASCASARJANA PRESS, 2019)
The objective of the research are : To calculate and analysis the impact of domestic consumption of fertilizer on gross value added , export of fertilizer on gross value added, consumption of fertilizer on labor absorption, export of fertilizer on labor absorption, import content of fertilizer domestic consumption and for export and calculate and analysis backward forward linkage of fertilizer sector. The method to be used is I-O of Leontief. The data is from BPS based on the year of 2010 as basic year. Disagregation is used from 66 sectors into 34 sectors where the sector of fertilizer is in the sector of 14. The result of the research are : (1) The impact of domestic consumption on gross value added in average of (2010-2014) is Rp. 5,437,970.8 million. (2) The impact of export on gross value added is Rp. 2,066,940.4 million. (3) The impact of domestic consumption on labor absorption (2010-2014) is about 16,194 people. (4) The impact of export on labor absorption is 13,170 people. (5) The import content for domestic consumption is Rp. 930,860.4 million, while for export is Rp. 756,999.8 million. (6) backward-forward linkage are 0,86 and 0,78 at 2010 and then backward-forward linkage are 1,03 and 1,77 at 2005, so fertilizer industry has not as key sector. The implication that The development of fertilizer industry should be optimized because Indonesia has the gas resources that could support the fertilizer industry. Plant investment is needed to increase production capacity of fertilizer industry so as to increase production factors such as employment, regional development and output of other sectors. In order to continuously produce fertilizer there need a guarentee for the supply of gas from government to fertilizer plant. Production of Fertilizer Industry should be inreased in Indonesia since domestic demand is greater than production. The value of forward and backward linkages have indexes greater less the one cause fertilizer industry has not priority industry for development and not interested for investment. The government must redefined strategy planning for fertilizer industry in order to contribute to agriculture and food self-sufficiency program